The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.humov.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the upper limb movement kinematics utilized by children playing virtual and real table tennis

Abstract: Active virtual games (AVG) may facilitate gross motor skill development, depending on their fidelity. This study compared the movement patterns of nineteen 10-12yr old children, whilst playing contributed to the differences in movement patterns observed. Understanding the interface components for AVGs may help development of higher fidelity games to potentially enhance the development of gross motor skill and thus participation in PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…With these measures, we found that the systematic addition of the naturalistic task’s components into the standard task still maintained strong concurrent validity, and supports previous findings (Danion and Sarlegna, 2007). While more detailed kinematic analyses of the hand’s path or individual limb segments/joints may have provided additional insights, we did not constrain movement patterns in order to afford self-selection in movement strategy and to allow the motion to be as naturalistic as possible (Reinkensmeyer, 2010); thus, the current study design likely yielded highly variable joint coordination patterns within and between participants (Adams et al, 2015; Bufton et al, 2014; Gates et al, 2012; Petuskey et al, 2007; Srinivasan and da Silva, 2011; Wisneski and Johnson, 2007) and multiple planning mechanisms (Desmurget et al, 1997; Scheidt and Rymer, 2000), which is consistent with goal-directed movement in daily life (Bailey et al, 2014). We therefore restricted our analyses to global temporal and spatial variables of the end effector in this study.…”
Section: Discussionmentioning
confidence: 99%
“…With these measures, we found that the systematic addition of the naturalistic task’s components into the standard task still maintained strong concurrent validity, and supports previous findings (Danion and Sarlegna, 2007). While more detailed kinematic analyses of the hand’s path or individual limb segments/joints may have provided additional insights, we did not constrain movement patterns in order to afford self-selection in movement strategy and to allow the motion to be as naturalistic as possible (Reinkensmeyer, 2010); thus, the current study design likely yielded highly variable joint coordination patterns within and between participants (Adams et al, 2015; Bufton et al, 2014; Gates et al, 2012; Petuskey et al, 2007; Srinivasan and da Silva, 2011; Wisneski and Johnson, 2007) and multiple planning mechanisms (Desmurget et al, 1997; Scheidt and Rymer, 2000), which is consistent with goal-directed movement in daily life (Bailey et al, 2014). We therefore restricted our analyses to global temporal and spatial variables of the end effector in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ebrahimi et al (2016) showed that participants were more accurate performing a reaching task in the real world compared to the virtual world. Bufton, Campbell, Howie, and Straker (2014) showed that when playing the same game (ping-pong) in the real world or in a virtual setting, participants exhibited different movement patterns across the two modalities. Their findings suggest that the difference in movement patterns may interfere with learning the real-world motor skill.…”
Section: Chapter Fourmentioning
confidence: 99%
“…Their performance (score) during each game at each data collection time point was included as an extraneous variable. AVG performance was evaluated as there may have been substantial gains in AVG skill without transfer to real-world skills (Bufton et al, 2014). Each game was played against a computer generated avatar on the easiest level and included a warm up period (length detailed below) where research staff provided encouragement and technique/game instruction where necessary.…”
Section: Additional Variablesmentioning
confidence: 99%
“…Therefore, the Kinect and Sony AVG systems, which use camera motion monitors to input full body movements, might be a more suitable AVG for home based DCD intervention. Given that movement fidelity has been demonstrated to differ between AVG consoles (Bufton, Campbell, Howie, & Straker, 2014), the use of multiple consoles would also allow a range of movement stimulations.…”
Section: Introductionmentioning
confidence: 99%